Contribuição ao estudo dos impactos da NBR 15575: 2013 no processo de gestão de projetos em empresas construtoras de pequeno e médio porte - Ana Cláudia Pereira Cotta Rezende (2017)
The improvement of the buildings Quality has being increasingly demanded by society in general, users and regulatory and supervisory institutions. The search for this quality, which can be defined as the search of the performance of buildings, had as a great stimulus the publication of the performance standard, ABNT: NBR 15575: 2013. The present work presents an exploratory study highlighting the design management process of residential buildings as regards NBR 15575:2013 requisites assurance. At the same time, tools and procedures for the management of the design process were developed, implemented and evaluated, in order to fit to the standard requisites. The results point out the challenges faced by the companies: lack of knowledge about the new standard and the requirements associated with the design process, lack of qualified designers, lack of technical information on materials and construction systems, design management process poorly structured, with poor procedures and control mechanisms. The difficulties presented highlight the need to change the market mechanisms giving more importance to early phases of Projects. There is also a demand for a well-developed design process, with qualified professionals and a collaborative environment. The tools developed take into account the improvement of the design process, presenting milestones and fundamental steps for design development, embracing procedures and mechanisms of control, aiming the performance, from the hiring of designers to the receipt, analysis and acceptance of the design disciplines. The tools evaluation suggests their usefulness in the context of the studied companies. This research brings contributions to the market, considering the presented tools, as well as at academic level, since there aren´t still many studies focusing on the integration of the design process and performance assurance.